Antihypertensive effects of astaxanthin - Hiroshi Yoshida; Kumie Ito; Hidekatsu Yanai; Norio Tada (Dove Medical Press, 2008)
Hidekatsu Yanai1,2, Kumie Ito1,2, Hiroshi Yoshida2,3, Norio Tada1,21Department of Internal Medicine; 2Institute of Clinical Medicine and Research; 3Department of Laboratory Medicine, The Jikei University School of Medicine, Chiba, JapanAbstract: Astaxanthin is a biological antioxidant naturally found in a wide variety of aquatic living organisms, and has shown various pharmacological activities, such as anti-inflammatory and antidiabetic activities. A recent study reported that the administration of astaxanthin induced a significant reduction in blood pressure and delayed the incidence of stroke in stroke-prone spontaneously hypertensive rats, suggesting that astaxanthin also has antihypertensive effect. In a study using aortic rings of spontaneously hypertensive rats, astaxanthin induced a significant reduction of the contractile responses of the aorta to α-adrenergic receptor agonist and angiotensin II, which may contribute to the antihypertensive effect of astaxanthin. In a histopathological study, astaxanthin decreased coronary artery wall thickness compared with the control, indicating the possibility that astaxanthin ameliorates hypertension-induced vascular remodeling. Astaxanthin has anti-inflammatory, antidiabetic, antihypertensive, and antioxidative activities; therefore, we should perform further studies to elucidate an antiatherogenic effect of astaxanthin.Keywords: astaxanthin, antioxidant, antihypertensive effect, atherosclerosis